Recursos vegetais nos quintais da Comunidade Saloba Grande, Porto Estrela (MT) : uma abordagem etnoecológica - Rocha, Douglas Braga (2013)
Among the elements considered in this context are set as the most important elements the backyards. The study was conducted at Community Saloba Grande (15 ° 37'37 .58''S and 57 º 15'04 .77''W) belonging to the municipality of Porto Estrela-MT (15 °19'28, 40''S and 57 º 13'07, 16''W), which in turn lies approximately 180 km from Cuiaba, capital of Mato Grosso. Many residents of this community are morroquianos, the ancient inhabitants of the Serra das Araras. For data collection was used the through semi-structured interviews. The sequence that community livers were interviewed was dictated by the method of Snow Ball (ball-ofsnow), a census was conducted in the community registering a total of 44 backyards. To test quantitatively the ethnobotanical informations, were used indes as Fidelity Level (FL) and Agreement on Use Primary (AUP). We found a richness of 305 species in 86 plant families. The most represented families were Asteraceae with 23 records, followed by Fabaceae with 22 and with 17 Solanaceae. The species also were divided into five ethnocategorys, being the food the most cited and medicine the more represented in relation to richness. Following this trend, the ethnocategorys with highest values of FL and AUP, mostly, are also food and medicinal.